2014
DOI: 10.1213/ane.0000000000000171
|View full text |Cite
|
Sign up to set email alerts
|

The Society for Obstetric Anesthesia and Perinatology Consensus Statement on the Management of Cardiac Arrest in Pregnancy

Abstract: This consensus statement was commissioned in 2012 by the Board of Directors of the Society for Obstetric Anesthesia and Perinatology to improve maternal resuscitation by providing health care providers critical information (including point-of-care checklists) and operational strategies relevant to maternal cardiac arrest. The recommendations in this statement were designed to address the challenges of an actual event by emphasizing health care provider education, behavioral/communication strategies, latent sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
1
31

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(93 citation statements)
references
References 78 publications
0
61
1
31
Order By: Relevance
“…These data clearly showed that maternal survival is related to the place of collapse. Current teaching suggests that PMCS should be performed within 5 minutes of maternal cardiac arrest, where cardiac output is not restored, to improve maternal outcome, with potential additional benefit to fetal outcome. Our data support this; however, we must accept that in many women, the delay in PMCS was because they collapsed at home and not due to a delay within a hospital setting.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…These data clearly showed that maternal survival is related to the place of collapse. Current teaching suggests that PMCS should be performed within 5 minutes of maternal cardiac arrest, where cardiac output is not restored, to improve maternal outcome, with potential additional benefit to fetal outcome. Our data support this; however, we must accept that in many women, the delay in PMCS was because they collapsed at home and not due to a delay within a hospital setting.…”
Section: Discussionmentioning
confidence: 83%
“…Dutch data suggest a reduction in the reluctance to perform PMCS as a result of maternity‐specific training; however, few were carried out within the prescribed 5 minutes and overall maternal survival was poor . American data show that up to one‐third of women who arrest die with their baby still in utero . We have shown a very different approach in the UK; 49 of the 66 women had a PMCS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ej., PEEP > 10 mm/Hg, FiO2: 100 %). Esta variable se construyó por consenso, con base en la experiencia del grupo investigador, y por aplicación de evidencia indirecta (manejo del paro cardiorrespiratorio y del síndrome de dificultad respiratorio agudo en el embarazo) (22,23).…”
Section: Variables Por Medirunclassified
“…Several guidelines provide practical advices concerning the treatment of maternal cardiac arrest, which are summarised in table 1 67 68. Immediate basic life support and, when available, advanced life support should be initiated as outside pregnancy.…”
Section: Arrhythmiasmentioning
confidence: 99%